Pemikiran Abu Yazid (Al-Ittihad) dan Al-Hallaj (Hulul) - Muhammad Rifky Akbar Sahrul; Indo Santalia (Rahmad : Jurnal Studi Islam dan Ilmu Al-Qur'an, 2024)
Sufism is a scientific field in which there have been many controversies and polemics in history and created the bonds we know today. In the course of the history of Sufism, almost all Islamic scholars and intellectuals agree that the existence of Sufism has existed since the time of the Prophet Muhammad SAW. Where most Muslims recognize it as a scientific field that cleanses the heart, or a means to bring humans closer to God, their creator. Sufism has changed from time to time. In the past, it was just morals and now it involves Aqidah, giving rise to many pros and cons. Ittihad and Hulul are two aspects that cannot be separated among Sufism scholars. What is meant by Ittihad is a level in Sufism where a Sufi feels he is one with his God, the Almighty Creator; a level where loving and being loved have become one, so that one of them can call one by saying: hi me, while Hulul is a teaching which states that God has chosen the human body, of course to reside in it with divine nature, after The human nature in his body is eliminated first